PERANCANGAN SISTEM INFORMASI MANAJEMEN KEUANGAN UNTUK PENGENDALIAN SIMPAN PINJAM DAN LAPORAN KEUANGAN DI KOPERASI SEMARANG - Tantik Sumarlin; Ari Susanti (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
This research is conducted to assist the performance of cooperatives by utilizing financial management information system for savings and loan management and financial report in Cooperatives. Data collection methods used in this study is to conduct interviews on the financial and secretary of the cooperative with the object of research on the Business Cooperative "OENGARAN TEMPO DOELOE SEJAHTERA". Activities undertaken by KSU "OTD Sejahtera" include savings and loan activities, waserda and trading units and services. The system development method used in this research is Research and Developmnet Borg and Gall, 1983 which consists of: Research and Information Collection, Planning, Develop Preliminary Form of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, Operational Product Revision , Operational Field Testing, Final Product Revision, Dissemination and Implementation. The result of the research shows that by utilizing financial management information system can help the cooperative in processing the data of saving and loan become more effective and efficient. Control of savings and loans and the preparation of financial statements can be presented quickly and accurately. System performance becomes more precise, valid and more optimal.